2015
DOI: 10.1371/journal.pone.0143333
|View full text |Cite
|
Sign up to set email alerts
|

MET Gene Amplification and MET Receptor Activation Are Not Sufficient to Predict Efficacy of Combined MET and EGFR Inhibitors in EGFR TKI-Resistant NSCLC Cells

Abstract: Epidermal growth factor receptor (EGFR), member of the human epidermal growth factor receptor (HER) family, plays a critical role in regulating multiple cellular processes including proliferation, differentiation, cell migration and cell survival. Deregulation of the EGFR signaling has been found to be associated with the development of a variety of human malignancies including lung, breast, and ovarian cancers, making inhibition of EGFR the most promising molecular targeted therapy developed in the past decad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 76 publications
1
35
0
Order By: Relevance
“…Among these three METamplified resistant cell lines, combined treatment with osimertinib and crizotinib was only effective in one of the cell lines. The detailed mechanisms underlying these results remain unknown, but they are consistent with a previous report that MET gene amplification and MET receptor activation are insufficient to predict a positive response of NSCLC cells to combined treatment with MET and EGFR inhibitors (44).…”
Section: Discussionsupporting
confidence: 88%
“…Among these three METamplified resistant cell lines, combined treatment with osimertinib and crizotinib was only effective in one of the cell lines. The detailed mechanisms underlying these results remain unknown, but they are consistent with a previous report that MET gene amplification and MET receptor activation are insufficient to predict a positive response of NSCLC cells to combined treatment with MET and EGFR inhibitors (44).…”
Section: Discussionsupporting
confidence: 88%
“…The results indicated that vitamin C is not efficient in enhancing MTX-induced cytotoxicity in tarceva-resistant TNBC cells. Previously, many studies showed that tarcevaresistant cells have EGFR gene mutations or additional bypass signaling pathways to activate downstream of EGFR (65,66). These mutation genes and bypass pathways are important factors for cell proliferation with EGFR inhibitor treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The human NSCLC cell lines HCC827 and HCC4006, which harbor EGFR activating mutations ( 16 , 17 ), were purchased from the Chinese Academy of Sciences (Shanghai, China). Both cell lines were cultured in RPMI-1640 medium (BioWhittaker ® ; Lonza Group, Ltd., Basel, Switzerland) supplemented with 10 mM HEPES, 1 mM L-glutamine, 100 U/ml penicillin/streptomycin (BioWhittaker ® ; Lonza Group) and heat inactivated 10% fetal bovine serum (FBS; Gibco; Thermo Fisher Scientific, Inc.) and grown at 37°C in a 5% CO 2 atmosphere.…”
Section: Methodsmentioning
confidence: 99%